Load-independent Class EF inverters for inductive wireless power transfer - Aldhaher,S; Mitcheson,PD; Yates,DC (IEEE, 2016)
This paper will present the modelling, analysis and design of a load-independent Class EF inverter. This inverter is able to maintain zero-voltage switching (ZVS) operation and produce a constant output current for any load value without the need for tuning or replacement of components. The load-independent feature of this inverter is beneficial when used as the primary coil driver in multi megahertz high power inductive wireless power transfer (WPT) applications where the distance between the coils and the load are variable. The work here begins with the traditional load-dependent Class EF topology for inversion and then specifies the criteria that are required to be met in order achieve load-independence. The design and development of a 240W load-independent Class EF inverter to drive the primary coil of a 6.78MHz WPT system will be discussed and experimental results will be presented to show the load-independence feature when the distance between the coils of the WPT system changes.